Hierarchical macropore-mesoporous shell carbon dispersed with Li4Ti5O12 for excellent high rate sub-freezing Li-ion battery performance. (April 2019) - Ho, Ching-Kit; Li, Chi-Ying Vanessa; Deng, Zhaofeng; Chan, Kwong-Yu; Yung, Hoi; Yang, Chunzhen
Abstract: The significant reduction in capacity and cyclability of lithium-ion batteries (LIBs) at low temperature is still limiting its application in cold climate. Limited literature has addressed the low temperature performance of LIB anodes, mostly restrict to low current performance showing low durability (<100 cycles). This is the first report of excellent durability in Li4 Ti5 O12 -based composite cycling at a high current (10C) over 1000 cycles under sub-zero temperatures. We embed Li4 Ti5 O12 nanoparticles in hierarchical macropore-mesoporous shell carbon network (HCMS carbon) to form Li4 Ti5 O12 /HCMS carbon nanocomposite. The HCMS carbon is an ideal support for Li4 Ti5 O12 to achieve excellent high rate sub-freezing LIB performance by providing short, intertwining Li-ion diffusion pathways between embedded Li4 Ti5 O12 particles and Li-ion reservoirs, and ample routes for continuous, multi-directional electron flow to Li4 Ti5 O12 particles. At −20 °C, the Li4 Ti5 O12 /HCMS carbon composite delivers the highest literature-reported specific energy of 80 Wh/kg at a high specific power of 3000 W/kg. This work demonstrates our Li4 Ti5 O12 /HCMS carbon composite can be a viable LIB anode material with fast and efficient Li-ion and electron transport active in sub-zero temperature operation. Graphical abstract: Image 1